2020
DOI: 10.1017/s0950268820002939
|View full text |Cite
|
Sign up to set email alerts
|

High MERS-CoV seropositivity associated with camel herd profile, husbandry practices and household socio-demographic characteristics in Northern Kenya

Abstract: Despite high exposure to Middle East respiratory syndrome coronavirus (MERS-CoV), the predictors for seropositivity in the context of husbandry practices for camels in Eastern Africa are not well understood. We conducted a cross sectional survey to describe the camel herd profile and determine the factors associated with MERS-CoV seropositivity in Northern Kenya. We enrolled 29 camel-owning households and administered questionnaires to collect herd and household data. Serum samples collected from 493 randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…MERS-CoV prevalence was the highest during October (autumn) in Iraq [ 26 ], and during winter in Saudi Arabia [ 27 ]. Camel herd size, dung removal frequency, adding new camels to the herd, presence of nasal discharge, exposure to wild animals, and owners' ethnic background could affect MERS-CoV RNA and IgG prevalence [ 25 , 28 , 29 ]. One study reported viral RNA in semen [ 30 ], raising the possibility of sexual transmission of the virus.…”
Section: Resultsmentioning
confidence: 99%
“…MERS-CoV prevalence was the highest during October (autumn) in Iraq [ 26 ], and during winter in Saudi Arabia [ 27 ]. Camel herd size, dung removal frequency, adding new camels to the herd, presence of nasal discharge, exposure to wild animals, and owners' ethnic background could affect MERS-CoV RNA and IgG prevalence [ 25 , 28 , 29 ]. One study reported viral RNA in semen [ 30 ], raising the possibility of sexual transmission of the virus.…”
Section: Resultsmentioning
confidence: 99%
“…These movements generate patterns of contact within populations that have important implications for the spread of pathogens. Therefore, the high abortion burden in ASALs likely reflected the numerous underlying challenges among livestock in these areas [ 18 , 21 , 22 ]. Given the role that livestock abortion plays in the transmission of zoonoses, identifying the predominant reservoir species of zoonotic pathogens and heightening surveillance sensitivity in ASAL zones are necessary steps toward minimizing zoonoses risk.…”
Section: Discussionmentioning
confidence: 99%
“…Tribal communities, such as the Somali, Gabra, and Borana in the eastern and northeastern regions of Kenya primarily focus on camels as a pastoral livelihood strategy due to the camel’s adaptability to arid environments and ability to withstand droughts (Ngere et al, 2020). Also, the Somali primarily inhabit the Northeastern region with high regard for camels for their annual religious practices and ritual migrations (Watson, 2010), and a greater number of cultural practices and traditions associated with livestock rearing, trade, and consumption in tribal communities (Dan et al, 2021; Kagunyu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%